Contested Moral and Political Authority on Instagram: Religious and State Actors’ Framing of Palestinian Humanitarian Narratives - Lubis, Abdul Haris; Sazali, Hasan; Ritonga, Hasnun Jauhari (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
This study examines the growing competition between religious and state actors in framing Palestinian humanitarian issues on Instagram. Previous studies on Palestinian digital activism on Instagram have generally emphasized emotional solidarity and content amplification but have failed to account for how religious and state actors directly compete for moral and political authority within the same platform space. Addressing this gap, this study aims to identify how these actors construct and contest narrative frames and how users negotiate meaning through their engagement patterns. Using a qualitative case study design, data were collected through analysis of high-engagement posts, semi-structured interviews with religious and institutional content producers, and documentation of digital footprints, which were analyzed through pattern matching within the frameworks of digital authority and moral legitimacy. Findings indicate that religious actors construct humanitarian narratives based on moral-emotional appeals and religious obligation, while state actors emphasize diplomacy, legality, and political stability. Public responses demonstrate selective alignment and open competition, which reinforce non-state narratives through heightened emotional engagement. This study enhances the comprehension of religion-state relations in digital environments by illustrating that legitimacy is not exclusively generated by formal institutions but is actively negotiated through narrative interactions, public sentiments, and platform visibility. In doing so, this research goes beyond previous studies of digital activism by positioning Instagram as an arena for contested moral and political authority, rather than simply a medium for mobilizing human solidarity.